Altmetrics in Institutional Repositories: New Perspectives for Assessing Research Impact - Rehemtula, Salima (2014)
Poster (and extended abstract) presented at the 13th International Conference "Libraries in the Digital Age (LIDA 2014)" held on 16-20th June, University of Zadar, Zadar, Croatia